Construction of a plasmid encoding chicken mitochondrial antiviral signaling (MAVS) gene - Mohamad Wali, Haryati Shila; Ideris, Aini; Omar, Abdul Rahman; Bejo, Mohd Hair (Faculty of Veterinary Medicine, Universiti Putra Malaysia, 2013)
The significance of the role of mitochondria incontending viral infection is gaining worldwide interest. Its ability to elicit molecular signals to other immune components enables new perspective in the development of novel antiviral agents. This study explored the possibility of isolating the mitochondrial antiviral signaling (MAVS) gene from chicken tissue and cloning it into cloning vector. Prior to cloning, RNA extraction was carried out from chicken samples and converted to cDNA. Polymerase chain reaction (PCR) amplified product was ligated to the vector pJET1.2. The resulting plasmid construct pJET1.2/CARDIF was then transformed into competent cells and later sequenced and analysed by restriction enzyme analysis. BLAST analysis of the construct yields 99% similarity with Gallus gallus CARDIF mRNA gene.